The individual and combined associations of health behaviours with health-related quality of life amongst junior high school students in China - Liu, Ze Hua; Wang, Yi Lin; Yu, Yue Shuang; Ren, Yan; Zhang, Tong; Liu, Hong Qing; Wu, Xiu Yun (Frontiers in Public Health, 2023)
Objectives: This study aimed to investigate the individual and joint associations of sedentary behaviour, physical activity (PA), sleep and breakfast eating on health-related quality of life (HRQoL) among Chinese junior high school students. Methods: Data were from 783 junior high school students who participated in a health behaviour and health survey in Jining city of Shandong province of China. HRQoL was measured by the EuroQol five-dimensional questionnaire, youth version (EQ-5D-Y). Multivariable logistic and linear regressions were applied to examine the associations between health behaviours and HRQoL. Results: Multivariable regression analyses showed that using a computer ≥ 2 hours a day (versus < 2 hours/day) is associated with increased likelihood of having health problems in the three EQ-D-Y dimensions, including walking, looking after self and doing usual activities. Lower PA is associated with more problems in feeling worried, sad or unhappy, and with a lower visual analogue scale (VAS) score. Students who had insufficient sleep time (e.g., < 7 hours/day), and skipped eating breakfast were more likely to experience lower HRQoL in the dimensions of having pain or discomfort, and feeling worried, sad or unhappy, and a lower VAS score than those students who had longer sleep time and no breakfast skipping. Students who reported having the combined ≥ 2 unhealthy behaviours relative to the peers with 0-1 unhealthy behaviours were more likely to have lower HRQoL. Conclusions: The findings in the present study underline the importance of promoting healthy behaviours in order to improve HRQoL among Chinese junior high school students.